A Review of the First Edition of the Book by Author Dr Helen Scott: - Silvana Ilievska (Grounded Theory Review: An International Journal, 2025)
Using Grounded Theory is a valuable, fun, colourful, easy-to-follow and engaging learning tool. The target audience for this book is anyone interested in learning about Grounded Theory. Those include a novice student at any level who is engaging in research and considering using Grounded Theory methodology, supervisors who are mentoring students considering or engaging with Grounded Theory and any other academic researcher who has an interest and desire to engage conceptually with theory development. Scott describes her book as ‘a conceptual tool, which can be used by anyone who wishes to generate theory, irrespective of their philosophical perspective’. It is a practical book that assists with learning how to generate a theory about people and how they behave in a given setting.